(untitled) (Proceedings OPTIMAL, 2024)
Background: DIII Nursing students are health students with a diploma level. Anxiety is a condition that can cause a person to feel uncomfortable, restless, afraid, worried, and uneasy followed by various physical symptoms. Chocolate contains phenethylamine which triggers the release of endorphin which can increase happiness. Chocolate contains serotonin, a natural anti-depressant. Methods: This study is a quantitative research with a quasi experimental design of one group pretest and posttest. The population in this study were 55 respondents. The sample in the study was 40 respondents. Inclusion criteria are DIII nursing students at the third level who compile scientific papers, students with anxiety> 20, follow the research from start to finish and do not have chocolate allergies. While the exclusion criteria are students who are not on leave, not sick, absent, and not taking anti-anxiety drugs. This study used the ZSAS anxiety questionnaire and 68g dark chocolate. Students consume 3x in one week. Researchers used the Wilcoxon non-parametric statistical test. Results: The results of this study were the most age at the age of 21 years as many as 22 respondents (55%) and the most gender was female as many as 28 respondents (30%). Bivariate results of pretest chocolate consumption with mild anxiety level 22 (55%), moderate 15 (37.5%), and severe 3 (7.5%). Whereas, posttest chocolate consumption with mild anxiety level 37 (92.5%), moderate 3 (7.5%) and severe 0 (0%). Based on these results, the effect of chocolate consumption on anxiety levels in DIII Nursing students in facing the final project.